2013
DOI: 10.1021/ac4012057
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Separation of Malaria-Infected Red Blood Cells in Various Developmental Stages

Abstract: Malaria is a serious disease that threatens the public health, especially in developing countries. Various methods have been developed to separate malaria-infected red blood cells (i-RBCs) from blood samples for clinical diagnosis and biological and epidemiological research. In this study, we propose a simple and label-free method for separating not only late-stage but also early-stage i-RBCs on the basis of their paramagnetic characteristics due to the malaria byproduct, hemozoin, by using a magnetic field gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 46 publications
0
94
0
1
Order By: Relevance
“…[87] Such strategy based on microfluidic magnetophoresis to examine paramagnetic signatures of blood cells was also recently utilized for disease diagnosis to differentiate and separate healthy RBCs from early- and late-stage malaria-infected RBCs. [88] …”
Section: Blood Cell Sorting Using Innovative Microfluidic Toolsmentioning
confidence: 99%
“…[87] Such strategy based on microfluidic magnetophoresis to examine paramagnetic signatures of blood cells was also recently utilized for disease diagnosis to differentiate and separate healthy RBCs from early- and late-stage malaria-infected RBCs. [88] …”
Section: Blood Cell Sorting Using Innovative Microfluidic Toolsmentioning
confidence: 99%
“…One of them is a microfluidic device that is cheap, requires less diagnosis time, uses small amounts of samples, and does not need a skilled technician. (4)(5)(6)(7)(8)(9)(10) Recently, hemozoin, produced by a malaria parasite invading red blood cells, is being considered as an alternative biomarker for malaria diagnosis. Many research studies demonstrated that malaria-infected red blood cells (iRBCs) show magnetic properties distinct from those of healthy red blood cells (hRBCs), as shown in Table 1, and many groups have already utilized this difference for detecting or separating iRBCs in a label-free manner on a high gradient of a magnetic field inside the microfluidic device.…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies demonstrated that malaria-infected red blood cells (iRBCs) show magnetic properties distinct from those of healthy red blood cells (hRBCs), as shown in Table 1, and many groups have already utilized this difference for detecting or separating iRBCs in a label-free manner on a high gradient of a magnetic field inside the microfluidic device. (4)(5)(6)(7)(8) However, the current design has some limitations, such as being a batch process, having low precision, or causing severe damage to iRBCs. One important issue to be resolved is the significant reduction in the magnitude of the magnetic force with distance from the magnet poles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Plasmodium falciparum -infected red blood cells (RBCs) showed significant differences in its cell deformation, magnetic, and electrical properties compared with uninfected RBCs(Guo et al 2012; Nam et al 2013; Soo Hoo et al 2004). Various platforms have been developed to sort infected RBCs based on their morphological changes.…”
Section: Introductionmentioning
confidence: 99%